State violence and legal accountability : the wait for justice - Begüm Yıldız, Ceylan (Routledge, 2025)
"This book pursues a critical perspective on the phenomenon of state violence and its legal unaccountability. Focusing on the role of myths, assumptions, and ghosts that surround the meaning of the state and performance of state violence, this book details a fresh perspective on that violence and its legal unaccountability. It asks: How does our understanding of the state reflect on the political demands and legal processes of accountability? To pursue this question, the book traces the political and legal aftermath of the police killing of a fourteen-year-old boy, Berkin Elvan, during the nationwide Gezi protests of the summer of 2013 in Turkey. Countervailing imaginaries of the state clash between the state officer's attempt to attribute personal responsibility to Elvan for his own death, and public demands for state accountability. Meanwhile, the prolonged legal process ensures that subjects who seek accountability find themselves in a long and exhausting legal battle which dominates their lives and transforms their subjectivity. As the Elvan family continues to wait for accountability and justice, this book suggests that waiting and suspense are key elements of legal performance in trials concerning state violence. As such, and unlike the usual reading of legal violence, which focuses on judgement, the book explores how this violence - and its implications for an understanding of justice and accountability - is bound to the very act of waiting. This critical interdisciplinary study of state violence and its legal handling will appeal to scholars and students from a wider range of disciplines including law, criminology, politics, sociology and political and legal philosophy"-- Provided by publisher.
Keywords: Elvan, Berkin, -- 1999-2014.; Government liability -- Turkey.; Justice, Administration of -- Turkey -- 21st century.; State-sponsored terrorism -- Law and legislation -- Turkey.; Protest movements -- Turkey -- History -- 21st century.; Turkey -- History -- Gezi Park Protests, 2013.; Turkey -- Politics and government -- 21st century.; elektronické knihy; electronic books